Pengaruh Pemberian Metode Kangaroo Mother Care (KMC) terhadap Respon Fisiologis pada Bayi BBLR - Intan Triyanti; Kurnia Wijayanti; Indra Tri Astuti (Pusat Riset dan Inovasi Nasional, 2025)
In general, LBW infants do not have a mature immune system to adapt due to the immaturity of the infant's organ systems. Improving the physiological response of LBW infants can be done using an inexpensive, easy-to-do, and effective intervention, namely the Kangaroo Mother Care (KMC) method. This study aims to determine the effect of the Kangaroo Mother Care (KMC) method on the physiological response of LBW infants. This study used a quasi-experimental study with a pretest-posttest with control group design. The sample size was 34 LBW infants born at Dr. H. Soewondo Kendal Regional General Hospital, obtained through an infinite population technique. Data were collected using observation sheets and bedside monitors. Data analysis was performed using a paired t-test to determine the effect of the Kangaroo Mother Care (KMC) method on the physiological response of LBW infants. The results showed that there was an effect of Kangaroo Mother Care (KMC) on temperature (p-value 0.000), respiratory rate (p-value 0.000), pulse rate (p-value 0.000) and oxygen saturation (p-value 0.000) in LBW babies. There was an effect of standard care on temperature (p-value 0.000), respiratory rate (p-value 0.006), pulse rate (p-value 0.028) and oxygen saturation (p-value 0.000) in LBW babies. There was a difference in the physiological response of LBW babies between those given KMC and the nesting care control group, where KMC showed a better physiological response with a temperature difference of 1,230C, respiratory rate of 5.41 x/minute, pulse rate of 9.65x/minute and 1,230C, respiratory rate of 5.41 x/minute, pulse rate of 9.65x/minute and oxygen saturation of 2.23%.